Effectiveness of Video-Based Self-Management Education in Reducing Psychological Stress and Blood Pressure among Hypertensive Patients in Primary Healthcare: A Quasi-Experimental Study - Prima Trisna Aji; Muhammad Nur Hasbi; Elinda Rizkasari (JURNAL KEPERAWATAN SUAKA INSAN (JKSI), 2026)
Video-Based Self-Management Education Reduces Psychological Stress and Blood Pressure in Hypertensive Patients. Hypertension is closely associated with psychological stress, which can impair blood pressure control and self-management capacity. This studyaimed to evaluate the effect of video-based self-management education on psychological stress and blood pressure among hypertensive patients. A quasi-experimental one-group pretest–posttest design was conducted involving 60 hypertensive patients who received a structured video-based self-management education intervention for four weeks. Psychological stress was measured using the Depression Anxiety Stress Scale-21 (DASS- 21), and blood pressure was assessed using a calibrated digital sphygmomanometer. Data normality was evaluated using the Shapiro–Wilk test. The results demonstrated a significant reduction in blood pressure based on the Paired Samples t-test (p < 0.001; 95% CI: ?55.83 to ?50.33), while psychological stress significantly decreased according to the Wilcoxon Signed Rank Test (p < 0.001). Video-based self-management education is aneffective and practical nursing intervention for improving both psychological and physiological outcomes among hypertensive patients in primary healthcare settings.